Efficacy of Late-Season Herbicide Programs for Controlling Palmer Amaranth in Postharvest Wheat Stubble - R. Liu; V. Kumar; N. Aquilina; T. Lambert (Kansas Agricultural Experiment Station Research Reports, 2020)
Late-season control of Palmer amaranth in wheat stubble is a challenge for Kansas producers. The objective of this study was to determine the effectiveness of POST herbicide programs (with multiple modes of actions) for late-season control of Palmer amaranth in postharvest wheat stubble. The study was conducted at the Kansas State University Agricultural Research Center in Hays, KS, in 2019. The study site had a natural seedbank of Palmer amaranth that emerged immediately after wheat harvest. All selected herbicide programs were tested 3 weeks after wheat harvest, when Palmer amaranth plants had attained a height of 2 to 2.5 feet with inflorescence initiation. Twenty-four herbicide programs comprising Roundup PowerMax, Clarity, 2,4-D, Aatrex, Gramoxone, Sencor, Valor SX, Spartan, Sharpen, Authority Supreme, Kochiavore, Panther MTZ, and Huskie applied alone or in tank-mixtures were tested at recommended-use rates. All herbicide treatments were arranged in a randomized complete block design with four replications. Visual Palmer amaranth control was assessed at 2, 4, and 8 weeks after treatment (WAT) by using a rating scale of 0–100% (where 0 = no control and 100% = complete plant death). The aboveground Palmer amaranth biomass and seed production were determined by harvesting plants from a 10.7-ft2quadrat placed at the center of each plot 8 WAT. All tested herbicide programs, except Kochiavore and a tank-mixture of Huskie + Aatrex provided>88% control of Palmer amaranth 8 WAT. In contrast, late-season control of Palmer amaranth did not exceed 71% at 8 WAT with Kochiavore or a tank-mixture of Huskie plus Aatrex treatments. Consistent with visual control (%), a majority of those tested programs significantly reduced shoot dry weights (>77% reduction) and seed production (>93% reduction) of Palmer amaranth compared to nontreated weedy check. Overall, these results suggest that several POST herbicide programs exist that growers can utilize for effective late-season control of Palmer amaranth in postharvest wheat stubble.
Keywords: Palmer amaranth; herbicide options; wheat stubble